The evaluation/application of Hydrus-2D model for simulating macro-pores flow in loess soil - Xuexuan Xu; Shahmir Ali Kalhoro; Wen yuan Chen; Sajjad Raza (International Soil and Water Conservation Research, 2017)
Soil hydraulic properties were mainly governed by soil structures especially when the structures is full of the connected soil macro-pores. Therefore, the good hydrological models need to be well documented for revealing the process of soil water movement affected by soil medium. The Hydrus-2D model with double domain was recommended in simulating water movement in a heterogeneous medium of soil. To evaluate the performance of the double domain Hydrus-2D model in loess soil, the dynamic of soil wetting front movement in differential loess soil columns under the constant water head were observed and the processes was simulated by Hydrus-2D model under conditions of different soil properties. The results indicated that the Hydrus-2D model was quite good in simulation of loess soil water movements, and the relative errors of simulation results are less than 15%, MRE less than 5%, and R2>0.9. The results provided the appropriate infiltration parameters of loess soil.